Pokémon Go as palimpsest: Creating layers of meaning through augmented reality - Clowater, Victoria (Loading, 2021)
In this paper, I employ the concept of the palimpsest of meaning (Bailey, 2007) to illustrate how Pokémon Go shapes and produces relations to place. Using ethnographic data from student players at the University of Guelph, I demonstrate how augmented reality (AR) gaming constructs a curated layer of place meaning that influences players’ knowledge of, relationships to, and movement through space. In so doing, I argue that we should not ignore the potential of AR technology to influence how we come to know place, emphasizing the impacts that biases, which are coded into this technology, might have on subaltern narratives of place and on marginalized communities, particularly in the context of Canadian settler colonialism and the erasure of Indigenous knowledge.